Effect of Nursing Intervention Package On Pre-Diabetic Status among Adults: A Systematic Review - Vishal k Ghorpade, Pravin Dani (South Eastern European Journal of Public Health, 2025)
Background: India is known as the diabetes capital of the world, with 64.5 million people living with diabetes. By 2030, this number is expected to rise to 87 million. This increase is largely due to lifestyle changes, including unhealthy eating habits and reduced physical activity. According to the International Diabetes Federation (IDF), more than half (66%) of Indians are unaware of their diabetic status, compared to 50% in Europe and 33% in the USA. Approximately 4.4 million Indians are unaware they have diabetes, putting them at higher risk of developing complications. A study by Ramachandran et al. revealed that for every known case of diabetes in India, there are 1.2 undiagnosed cases. Another study by Khan et al. highlighted that early screening for diabetes can significantly improve the quality of life and increase life expectancy for individuals over time. Methods and Materials:To gather information, 130 research articles were reviewed from databases like PubMed, Google Scholar, Cochrane Library, Academia, Open Access, and the Directory of Open Access Journals. The keywords “Prediabetes” and “Intervention Package” were used to search for relevant studies. After applying inclusion and exclusion criteria, 15 studies were selected for detailed analysis. The systematic review was conducted following the PRISMA guidelines, which are standard procedures for reviewing and reporting studies. Results:The majority of the studies used a quasi-experimental design with pretest-posttest control groups. Sample sizes varied from 30 to 400 participants, with one study involving 549 participants. Most studies collected data using the Indian Diabetes Risk Score (IDRS), HbA1c levels, and fasting blood sugar (FBS) tests. All the studies concluded that intervention packages were effective in managing prediabetes and preventing its progression to diabetes. Conclusion: India is facing a serious diabetes problem, with many people unaware of their condition, increasing their risk of complications. This review shows that early screening and intervention can help prevent prediabetes from turning into diabetes. Studies using tools like IDRS, HbA1c, and FBS confirmed that intervention programs are effective in managing prediabetes. These findings highlight the need for lifestyle changes and awareness programs to address this growing issue. By adopting such strategies on a larger scale, we can improve the quality of life for people at risk and reduce the impact of diabetes in India.